THE USE OF FOUR-SQUARE WRITING TO IMPROVE THE WRITING ABILITY OF DESCRIPTIVE TEXTS BY THE FIRST YEAR (X.1) STUDENTS OF SMA NEGERI 4 PEKANBARU - Felci Tria Sauhana (EJI (English Journal of Indragiri) : Studies in Education, Literature, and Linguistics, 2020)
This research aims to know whether Four-Square Writing Method could improve the students' ability in writing descriptive texts and also the factors that contribute to the improvement. The writer collected the quantitative data by using writing tests and qualitative by using observation sheets and field notes. The minimum criteria of the successful action were 75. Before applying the Four-Square Writing Method, the students were given a pre-test to know their writing ability or their base score. After applying the Four-Square Writing Method, the students' score increased from pre-test to post-test 1 and post-test 2. Based on the data analysis, the students' score improved from 68,97 in the pre-test, to 72,77 in the post-test 1 and 75,40 in post-test 2. Furthermore, based on the data analysis of students' observation sheet, there is a significant functional improvement of students' activities during teaching and learning process from Cycle 1 (58,05% ) to Cycle 2 (82,18%). Besides, based on the data analysis of teacher’s observation sheet, it also proved that there was a good improvement from teacher’s activities in Cycle 1 (72,22%) to Cycle 2 (91,67% ). Therefore, the use of Four-Square Writing Method can improve the ability to write descriptive texts by the first year (X.1) students of SMA Negeri 4 Pekanbaru.